Loss of PIKfyve Causes Transdifferentiation of Dictyostelium Spores Into Basal Disc Cells - Yamada, Yoko; Forbes, Gillian; Du, Qingyou; Kawata, Takefumi; Schaap, Pauline (Frontiers in Cell and Developmental Biology, 2021)
The 1-phosphatidylinositol-3-phosphate 5-kinase PIKfyve generates PtdIns3,5P2 on late phagolysosomes, which by recruiting the scission protein Atg18, results in their fragmentation in the normal course of endosome processing. Loss of PIKfyve function results in cellular hypervacuolization in eukaryotes and organ failure in humans. We identified pikfyve as the defective gene in a Dictyostelium mutant that failed to form spores. The amoebas normally differentiated into prespore cells and initiated spore coat protein synthesis in Golgi-derived prespore vesicles. However, instead of exocytosing, the prespore vesicles then fused to form the single vacuole that typifies the stalk and basal disc cells that normally support the spores. This process was accompanied by stalk wall biosynthesis, loss of spore gene expression and overexpression of ecmB, a basal disc and stalk-specific gene, but not of DDB_G0278745, a stalk-specific gene. Transdifferentiation of prespore into basal disc cells was previously observed in mutants that lack early autophagy genes, like atg5, atg7 and atg9. However, while autophagy mutants specifically lacked cAMP induction of prespore gene expression, pikfyveˉ showed normal early autophagy and prespore induction, but acted additively to the basal disc inducer DIF-1 to upregulate ecmB expression. Combined, the data suggest that the Dictyostelium endosomal system influences cell fate by acting on cell type specific gene expression.